Distribution of underwriting surplus and investment profit from tabarru' fund: Shariah contracts applied and current market practice - Ibrahim, Ahmad Basri; Mohd Ali, Ahmad Fadhil Hamdi; Elias, Mohd Hafizal; Wan Ahmad Lotfi, Wan Ahmad Najib (Australasian Journal of Islamic Finance and Business (AJIFB), 2015)
Takaful is a contract whereby the participants commit to contribute an amount on regular basis or in one lump sum in a specified fund to mutually guarantee each other and appoint a body to act as the fund manager. In this contract, Takaful participants have the opportunity to mitigate the possible financial risk that their families might encounter in case of misfortune. The contribution then will be placed into respective participant’s account or also known as Participants’ Investment Fund (PIF). The fund manager, i.e. Takaful operator will drip from every PIF an amount on the basis of donation into a collective Participants’ Risk Fund (PRF) or known as Tabarru’ Fund. This fund does not belong to the Takaful operator; it’s rather owned by the participants. The Takaful operator only manages the fund on behalf of the participants. Being a fund, money in it is also invested and would possibly generate profit. At the same time, with proper management of the Tabarru’ fund, it might produce surplus after payment of claims at the end of financial year. There are several Shariah views and methods on the treatment of the investment profit and underwriting surplus generated from the fund. These views differ from one to another depending on the contracts adopted, which ultimately would define the permissibility of sharing the profit and the surplus between related parties. In Malaysia, the sharing of underwriting surplus is allowed according to the resolution passed by Central Bank of Malaysia (Bank Negara Malaysia) subject to the certain guidelines. All eleven (11) Takaful operators in Malaysia have different practices in distributing the surplus and profit with respect to Shariah contracts applied and operational treatments. This research will study these differences and provide recommendations on the issues identified.